MATINYA 'PASAL KARET' UU ITE: BENARKAH ERA BARU KEBEBASAN BERPENDAPAT TELAH TIBA? - Zakki Alif; Khoirul Mujtahid; Dwi Ratna Cinthya dewi (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
The rapid growth of digital technology has created broader opportunities for people in Indonesia to express their opinions and ideas freely. Nevertheless, this development has also generated various legal issues, particularly concerning several provisions in the Electronic Information and Transactions Law (ITE Law) that are often referred to as “rubber articles” due to their vague and multi-interpretable nature. The amendment of the ITE Law through Law Number 1 of 2024 is viewed as the government’s effort to clarify legal norms so that they are no longer easily used to suppress public criticism and expression within digital spaces.This study aims to analyze whether the revision truly represents the beginning of a new phase of freedom of expression in Indonesia. The research applies a normative legal method using both statutory and conceptual approaches. The data were obtained from legislation, legal literature, academic journals, and court decisions related to the implementation of the ITE Law.The findings reveal that the revision has introduced several important changes, particularly in clarifying the elements of criminal offenses and narrowing overly broad interpretations of certain provisions. However, the possibility of criminalizing digital expression still remains because the boundaries between criticism, defamation, and harmful online content have not been clearly defined. Therefore, legal reform should be accompanied by a more democratic law enforcement culture that prioritizes the protection of human rights.